Efforts To Increase Student Numbers and Retain Students To Improve The Quality Of Globe National Plus School - Herianto Wiranata (ConCEPt - Conference on Community Engagement Project, 2021)
This study aims to determine the strategies applied to increase the number of students at Globe National Plus School by using a marketing mix promotion strategy. This study used qualitative research which initially made observations of the school environment to collect data, interview the school, and carry out documentation to become evidence of observations in the school environment. The main informants in this study were the Globe National Plus school foundation, the vice principal of the Globe National Plus school, the Globe National Plus subject teachers, the Globe National Plus students and parents. The data processing procedure starts from collecting data, presenting the observed data, and presenting the data by forming a conclusion. The strategy used in this school to improve marketing efficiency for Globe National Plus School is to promote schooling with social media by paying attention to the conditions of the school environment. With this research, it is hoped that all members of this school will participate in the promotion of the Globe National Plus school by enhancing the image of the school which makes the school better known to the public.